2022
DOI: 10.1111/cid.13153
|View full text |Cite
|
Sign up to set email alerts
|

Survival and complications of zygomatic implants compared to conventional implants reported in longitudinal studies with a follow‐up period of at least 5 years: A systematic review and meta‐analysis

Abstract: Background Zygomatic implants (ZI) have been frequently indicated to rehabilitate patients with extensive atrophies in alternatives to major bone reconstructions. It can be installed inside the maxillary sinus, called instrasinus zygomatic implant (IZI) or outside the maxillary sinus (EZI), depending on the surgery technique. Objective To evaluate the survival and complication rates of ZI in longitudinal studies when compared with conventional implants (CI). Methods An electronic search was performed in five d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
(114 reference statements)
0
4
0
Order By: Relevance
“…The incidence rate of OST could be caused by the intra-sinus path and lack of surrounding bone due to the palatal entrance. In recent systematic reviews, the frequency of this complication varies between 1.5 and 7.5% [ 17 , 20 ]. One study found fistula formation in 3 patients with no persisting fistula after a 3-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence rate of OST could be caused by the intra-sinus path and lack of surrounding bone due to the palatal entrance. In recent systematic reviews, the frequency of this complication varies between 1.5 and 7.5% [ 17 , 20 ]. One study found fistula formation in 3 patients with no persisting fistula after a 3-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Although the OST was a rather generic description of zygomatic implant position, in recent publications defined zygomatic implant positions for different anatomical situations are suggested (“Anatomy-Guided” techniques. Current systematic reviews were primarily aimed at comparing the survival rates with ZI treatment in different levels of atrophy maxillae, such as the classic approach versus the quad approach or ZI rehabilitation versus regular implant restoration [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1990s, zygomatic implants (ZI) have been used to rehabilitate atrophic maxillae [ 1 ] and reconstruct maxillary defects [ 2 ]. They have demonstrated commendable survival rates [ 3 6 ] and emerged as an alternative to extensive bone grafting [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The reported survival rate of zygomatic implants ranges between 89.9% and 96.5% 8,9 . Maxillary sinusitis is the most frequent late complication of zygomatic implants, with a reported incidence of 0%–26.6% 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…6,7 The reported survival rate of zygomatic implants ranges between 89.9% and 96.5%. 8,9 Maxillary sinusitis is the most frequent late complication of zygomatic implants, with a reported incidence of 0%-26.6%. 10,11 We previously showed that the Schneiderian membrane thickness (SMT) increases after zygomatic implant placement.…”
Section: Introductionmentioning
confidence: 99%